ADSORPSI MINYAK SEREH DAPUR MENGGUNAKAN BENTONIT (Lemongrass Oil Adsorption Using Bentonite) - Supardan, Muhammad Dani; Fatanen, Arief; Erika, Cut (Baristand Industri Banda Aceh, 2015)
Lemongrass (Cymbopogon citratus) is one of the plants which produce essential oil. Thequality of the essential oil can be determined from the physiochemical properties of the oil. In this study,chemical purification method is implemented by using bentonite as adsorbent. The Completely RandomDesign (CRD) factorial consisted of two factors is used in statistical data analysis. The first factor whichis observed is the time of adsorption (T) which is consisted of 4 levels which are T1 = 30 minutes, T2 = 60minutes, T3 = 90 minutes, and T4 = 120 minutes. The second factor is the absorbent concentration whichis consisted of 3 levels which are K1 = 1%, K2 = 5%, and K3 = 10%. The result of this study showed thatpurification using bentonite can improve the quality of the oil. Time of adsorption and adsorbentconcentration influenced the yield of lemongrass oil (Pâ¥0,01). The physical properties of the oil producedwere in accordance with the Essential Oil Association of America standard. Adsorption processes notonly reduce the citral content of lemongrass oil, however, also reduce the content of non-oxygenatedterpenes which can damage the quality of the lemongrass oil.